Expanding Infrastructure And Environmental Protection – Indissoluble Contradiction Or Reasonable Symbiosis? - Herber, Franz-Rudolf (European Scientific Journal, ESJ, 2016)
The expanding of infrastructure (roads/energy) is necessary as well in the developed countries as well as in the emerging countries: But the approach is different: In the developed countries the preservation of the given infrastructure is more important than new infrastructure. In the emerging countries necessary infrastructure is lacking and should be erected. Nevertheless, the management of such measures have to take the protection of environment into account. Those, who do not have any respect for nature, are behaving wrong. The belief, that such behaviour does not have any negative effects, is wrong. Nature does not endure any maltreatment and cannot endlessly recycle itself. But nature is a power that might be underestimated: If nature takes revenge on mankind, the consequences are drought, tornados and the drop of the sea level. Of course, if ones does have a religion, the answer has to be that the revenge of God will be severe, the Bible does call it apocalypsis or the end the world.